Uso do alendronato de sódio tópico associado ao Bio-Oss® no reparo de defeitos ósseos em calvária de ratos - estudo microtomográfico - Weigert, Natália Marreco (2016)
Introduction: Sodium alendronate (ALN) have demonstrated an anabolic effect on bone healing when associated with grafts from lyophilized bovine bone, but the administration procedures and concentration are still under investigation. Objective: This study evaluated the effects of topical use of 0.5% ALN, isolated or in association with Bio-Oss®, in repair of rat calvaria bone defects, through micro tomographic images (micro-CT). Methodology: Two 5 mm diameter cavities (right and left) were made on 18 Wistar rat’s skulls, totaling 36 bone defects filled according to each group (n = 9): Group A (GA) = 0.5% ALN placed with gelatin sponge; group B (GB) = Bio-Oss®; group AB (GAB) = Bio-Oss® blended 0.5% ALN; control group (CG) = blood clot. The animals were euthanized at 90 days postoperatively. The specimens were subjected to scanning by micro-CT. The three-dimensional quality parameters (total tissue volume, volume density and bone volume) and bone microarchitecture (number of trabecular bone, trabecular thickness and space between trabecular bone) were analyzed. To compare the groups, the Tukey test was applied (p ≤ 0.05). Results: The GB group showed statistically higher bone volume (12.74 ± 1.77 mm3 ) than the control group (8.99 ± 2.58 mm3 ; p = 0.016). GAB group presented significantly higher number of bone trabeculae (0.97 ± 0.28 mm-1) than GA and GC groups (0.64 ± 0.14 mm-1 and 0.65 ± 0.14 mm-1,respectively; p = 0.03). GA group shown more trabecular thickness (0.58 ± 0.09 mm) and statistically different than GAB group (0.45 ± 0.08 mm; p = 0.017). There was no significant difference between the groups regarding the total tissue volume, volumetric bone density and the spacing of the trabecular bone. Conclusion: 0.5% ALN isolated promoted fewer trabecular bone, but them were thicker when associated with Bio-Oss®. Add 0.5% ALN in Bio-Oss® did not modify the spacing between the bone trabeculae and the quality parameters obtained by microCT.